POLITIK HUKUM PERLINDUNGAN NELAYAN TRADISIONAL TERHADAP ILLEGAL FISHING - Andi Putra Sitorus; Dearma Sinaga (Ilmu Hukum Prima (IHP), 2022)
The wealth of fisheries in Indonesia is very large, because Indonesia's ocean area is very wide covering two-thirds of the total territory of the State of Indonesia. This wealth will become useless when it only becomes an easy target for illegal fishing actors, whether it is carried out by corporations or individuals from foreign countries or within their own country. Traditional fishermen are always on the disadvantaged side because of their weak position both managerially and the lack of facilities and infrastructure they have. The government must make policies in the form of legal politics in favor of traditional fishermen, so that traditional fishermen are the spearhead of the management of Indonesia's marine wealth. The method used in writing this thesis is to use a normative juridical approach. The types of data used are primary data, secondary data, and tertiary data. While the method of data collection is done through library research (Library Research). The results of this study show us that the government has made legal policies/politics to protect traditional fishermen in the form of products of laws and regulations at the level of laws and regulations below. In addition, there are also several direct policies carried out in the field related to efforts to protect traditional fishermen related to illegal fishing.